PP.05.17: INCIDENCE, DETERMINANTS AND MORBI/MORTALITY OF NEWLY DIAGNOSED DIABETES MELLITUS TYPE 2 IN HYPERTENSIVE PATIENTS. (June 2015) - Sala, E. Rodilla; Escrivá, M.; García, J.; Costa, J.A.; Pascual, J.M.; Sala, E. Rodilla
Abstract : Objective: The primary objective was to determine the incidence of newly diagnosed Diabetes mellitus type 2 (DM2) in hypertensive patients as well as to assess their morbi/mortality compared to non-diabetics. Secondary objective was to identify variables associated with the appearance of DM 2. Design and method: Observational, longitudinal, retrospective study of hypertensive patients treated at a Hypertension Unit, between the years 1986 and 2014. A total of 5877 were recruited. 1485 (25, 3 %) with baseline DM2 and further 386 patients (8, 8 %) with previous cardiovascular event were excluded, 446 patients (12, 1 %) were lost from follow-up, study population consisted finally of 3242 non-diabetic, hypertensive patients with at least 12 months follow-up. DM2 was defined either as fasting glucose > 125 mg/dl or HbA1c > 6, 5 %. The differences in time between visits in each patient and between patients were very variable. To account for these differences, repetitive measures according to the program STATA were used. Results: Mean follow-up time was 4, 9 years. At baseline mean age was 53, 2 years, 1758 patients (53, 8 %) were women, 19, 1 % were current smoker, 1797 patients (54, 6 %) were treated, average number of antihypertensives was 1, 2 drugs. At follow-up 2769 patients (84, 7 %) were under pharmacologic treatment, mean number of drugs was 1, 9. 459 (14, 0 %) patients became diabetic (2, 9 / 100 patient-years). Associated, independent factors in multivariate analysis related to developing DM2 were age (HR 1, 01; p = 0.03), HOMA index (HR 1, 01; p < 0.001), elevated fasting glucose (HR 4, 9; p < 0.001), BMI > 30 kg/m2 (HR 1, 7; p < 0.001), CRPus > 1, 5 mg/dl (HR 1, 3; p = 0.047), use of betablockers (HR 1, 4; p < 0.02), use of HCTZ (HR 1, 5; p < 0.003) and use of fibrates (HR 2, 3; p = 0.001). Cardiovascular events during subsequent follow-up were documented in 71/459 patients (15, 6 %) who became diabetics vs. 178/2609 patients (6, 4 %) who did not, showing so a 2, 4-fold higher probability of events. Conclusions: During a follow-up of almost 5 years, the proportion of hypertensive patients becoming diabetic was 14 %, the incidence of cardiovascular events was 2, 4-fold in these patients compared to non-diabetic hypertensives.